Effect of malaria on placental volume measured using three-dimensional ultrasound: a pilot study. - Rijken, M; Moroski, W; Kiricharoen, S; Karunkonkowit, N; Stevenson, G; Ohuma, E; Noble, J; Kennedy, S; McGready, R; Papageorghiou, A; Nosten, F (BioMed Central, 2012)
The presence of malaria parasites and histopathological changes in the placenta are associated with a reduction in birth weight, principally due to intrauterine growth restriction. The aim of this study was to examine the feasibility of studying early pregnancy placental volumes using three-dimensional (3D) ultrasound in a malaria endemic area, as a small volume in the second trimester may be an indicator of intra-uterine growth restriction and placental insufficiency.